EFFECTIVENESS OF CONCEPT MAPPING ON STUDENTS’ ACADEMIC ACHIEVEMENT IN BIOLOGY AT THE SECONDARY SCHOOL LEVEL - Sharma, Jyoti; Sharma, Ruby (International Journal of Research -GRANTHAALAYAH, 2025)
Concept mapping is a powerful visual learning strategy that allows students to organize and structure information meaningfully. By representing relationships between concepts through diagrams, concept mapping enhances comprehension, memory retention, and critical thinking. This exploratory study investigates the effectiveness of concept mapping on the academic achievement of IX standard students in the topic The Cell in a secondary school in Moradabad. The study involved 60 students, who were divided into two groups—control and experimental—each comprising 30 students. A pre-test designed by the researcher was administered to assess the baseline knowledge of all participants. Following this, the control group received instruction through traditional teaching methods, while the experimental group was taught using concept mapping techniques, which involved the creation and discussion of visual concept diagrams to represent cellular components and their functions. After the instructional period, a post-test was conducted for both groups using the same test structure as the pre-test. The scores were analyzed statistically to determine if there was a significant difference in academic performance between the two groups. Results revealed that students taught through concept mapping performed significantly better than those taught through traditional methods. The experimental group showed improved comprehension and higher retention of the topic. These findings suggest that concept mapping is not only an effective instructional tool but also a student-centered strategy that promotes meaningful learning, especially in subjects like biology that involve abstract and complex content. In conclusion, this study supports the integration of concept mapping into secondary school science education. It demonstrates that when students actively engage in constructing knowledge visually, their ability to understand and retain information improves, thereby enhancing overall academic achievement.